Effects of axial loads and higher order modes on the seismic response of tall bridge piers. (15th November 2021) - Tubaldi, E.; Scozzese, F.; De Domenico, D.; Dall'Asta, A.
Highlights: Seismic time-history analyses of tall piers by using an efficient analytical formulation. Extensive parametric study to evaluate the influence of axial loads and higher order modes. In-depth analysis of 3 case studies with different geometrical/mechanical/dynamic conditions. Critical assessment of Eurocode 8 simplified design approach for tall piers. Findings useful for a more informed design and assessment of bridges with tall piers. Abstract: Tall piers are essential components of the earthquake resisting system of bridges. The dynamic behaviour of tall piers differs significantly from that of short piers due to a number of factors, such as their high flexibility and inertia. This paper aims to quantify the influence of axial loads and higher order modes on the seismic response of bridges tall piers and to provide results useful for a more informed design and assessment. For this purpose, an analytical formulation of the dynamic problem, developed and validated in a previous study, is employed to analyse a wide range of piers and bridge configurations. In the first part of the paper, a thorough parametric investigation is carried out to evaluate the influence of axial loads and higher order modes on both the modal properties and the seismic response of tall piers with different geometries and vertical loads. Subsequently, three realistic case studies representing bridges with different geometrical, mechanical and dynamic conditions are analysed and seismic time-history analyses are performed to further investigate the problem. The obtained results provide useful insights into the seismic behaviour of bridges with tall piers, identify the relevant governing parameters and shed light on the accuracy of simplified approaches suggested by the Eurocode 8 to account for the second order effects.